Ovarian stimulation and oocyte cryopreservation in females and transgender males aged 18 years or less: a systematic review - Slonim, Marnie; Peate, Michelle; Merigan, Kira; Lantsberg, Daniel; Anderson, Richard A.; Stern, Kate; Gook, Debra; Jayasinghe, Yasmin (Frontiers in Endocrinology, 2023)
Background: Fertility preservation is an important healthcare focus in the paediatric and adolescent population when gonadotoxic treatments are required. Ovarian stimulation (OS) resulting in oocyte cryopreservation is a well-established fertility preservation option in the adult population. It’s utility, however, is little known in young patients. The purpose of this review was to synthesise the available literature on OS in patients ≤18 years old, to identify gaps in current research and provide suggestions for future research directions. Methods: Using PRISMA guidelines, a systematic review of the literature was performed for all relevant full-text articles published in English in Medline, Embase, the Cochrane Library and Google Scholar databases. The search strategy used a combination of subject headings and generic terms related to the study topic and population. Two reviewers independently screened studies for eligibility, extracted data and assessed the risk of bias. Characteristics of the studies, objectives and key findings were extracted and summarised in a narrative synthesis. Results: Database search and manual review identified 922 studies, 899 were eliminated based on defined exclusion criteria. Twenty-three studies were included and comprised 468 participants aged ≤18 years who underwent OS (median 15.2, range 7-18 years old). Only three patients were premenarchal, and four patients were on treatment to suppress puberty. Patients had OS for a broad range of indications including oncology treatment, transgender care and Turner syndrome. A total of 488 cycles of OS were completed, with all but 18 of these cycles (96.3%) successfully resulting in cryopreserved mature oocytes (median 10 oocytes, range 0-35). Fifty-three cycles (9.8%) were cancelled. Complications were rare (<1%). One pregnancy was reported from a female who had OS aged 17 years old. Conclusion: This systematic review demonstrates that OS and oocyte cryopreservation is achievable in young females however there are only a few cases in the literature describing OS in premenarcheal children or those who have suppressed puberty. There is little proof that OS can lead to pregnancy in adolescents, and no proof that this can be achieved in premenarchal girls. Therefore it should be regarded as an innovative procedure for adolescents and experimental for premenarcheal girls.